SOCIO-PSYCHOLOGICAL FACTORS OF PROFESSIONAL BURNOUT AMONG EMPLOYEES OF THE SES OF UKRAINE IN THE CONTEXT OF MODERN CHALLENGES - Liashch, Oksana; Yatsіuk Mariia; Hrebenova, Valentyna (Personality and environmental issues, 2025)
The article examines the socio-psychological factors of professional burnout among employees of the State Emergency Service of Ukraine (SES) in the context of modern challenges. In particular, the emphasis is placed on a comprehensive analysis of internal and external factors that cause emotional exhaustion, loss of motivation and a decrease in the professional efficiency of rescuers. The relevance of the chosen topic is due to the increasing level of stress in the professional environment of the SES, especially in martial law, the growing number of emergencies, psychological instability and information pressure.The aim of the study is to identify the main socio-psychological factors of professional burnout, analyse their interaction and determine practical recommendations for the prevention and overcoming of this syndrome among rescuers. The study used the author's questionnaire, which allowed us to study the emotional state, level of motivation, degree of social support and overall psycho-emotional stress of SES employees. The study involved respondents of different ages, genders, and length of service, which allowed us to obtain representative data on the state of mental health in the emergency services system. The results of the survey indicate a systemic spread of symptoms of professional burnout among service employees. A significant proportion of respondents reported regular emotional exhaustion, reduced motivation to perform their professional duties, and a lack of support from their superiors and colleagues. The level of stress associated with current challenges, such as the war, was assessed by respondents as high. Of particular note is the fact that only a small proportion of rescuers have undergone psychological training or received professional help after traumatic events.The analysis of burnout factors showed that the main determinants include chronic stress, a high level of responsibility for the lives of others, frequent contact with traumatic events, lack of resources for psychological recovery, and devaluation of the profession in the public consciousness. The researchers note that in conditions of constant danger and tension, the prerequisites for the development of secondary traumatisation are formed, which is also part of the burnout syndrome. The paper provides an overview of modern psychotherapeutic approaches to the prevention and correction of burnout. In particular, the article examines the effectiveness of cognitive behavioural therapy, which focuses on changing destructive thought patterns; humanistic approach, which focuses on finding the meaning of professional activity; psychodynamic therapy, which allows working through deep conflicts and traumas; and organisational and social approach, which offers changes in working conditions, improved communication in the team and the development of an incentive system.The importance of creating sustainable psychological support structures in the SES, implementing regular preventive measures, organising crisis interventions after difficult calls, and establishing effective cooperation between psychologists, managers and rescuers is also highlighted. Practical tools, such as relaxation techniques, art therapy, mindfulness practices and intervention meetings, have already proven to be effective in reducing the level of professional stress and improving the overall psycho-emotional state of employees.Summarising the results, the authors argue that the prevention and correction of professional burnout should be a systematic and multilevel process that combines individual, group and organisational measures. The implementation of such approaches will help to preserve the mental health of rescuers, increase their effectiveness and resilience to stress in conditions of constant threat and emergency situations.